1957
DOI: 10.1002/pol.1957.1202310339
|View full text |Cite
|
Sign up to set email alerts
|

Viscometric and conductometric titrations of polymethacrylic acid with alkali metal and quaternary ammonium bases

Abstract: The reduced specific viscosity of polymethacrylic acid increased with counterion size at the same degree of neutralization for the cations: sodium < tetramethylammonium < tetraethylammonium < tetrapropylammonium < tetrabutylammonium. The increase on going from sodium to tetrapropylammonium at 50–70% neutralization was 20–25% for 0.003–0.01 M polymer, about 4% in 0.001 M solutions. These data indicate that a significant fraction of even large counterions are close to the chain. Conductometric titrations showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…This is exactly in the same direction indicated by the present data. The existence of an optimum content of ionic groups in the polyacrylamide polymer to the drag reduction observed seems to be related to the literature results reported for poly(acrylic acid) (9) and poly(methacrylic acid) (10). These results showed that the reduced viscosity of both poly(acrylic acid) and poly(methacrylic acid) increased sharply with an increase of neutralization up to 40% and then decreased with further neutralization.…”
Section: Resultssupporting
confidence: 82%
“…This is exactly in the same direction indicated by the present data. The existence of an optimum content of ionic groups in the polyacrylamide polymer to the drag reduction observed seems to be related to the literature results reported for poly(acrylic acid) (9) and poly(methacrylic acid) (10). These results showed that the reduced viscosity of both poly(acrylic acid) and poly(methacrylic acid) increased sharply with an increase of neutralization up to 40% and then decreased with further neutralization.…”
Section: Resultssupporting
confidence: 82%
“…Experimental evidence of this dependency has been reported for polystyrenesulphonates [28], but was not found for polymethacrylate salts [a]. Experimental values of X of acrylic polyacids in salt-free solutions are in the range from 40 to 60 S.rnol-l.cm2 [19,29,30].…”
Section: Association Phenomenamentioning
confidence: 81%
“…There is no agreement on the dependency of X on a (which is linearly related to P n f ) . A small change of X with a has been reported [8,18] for poly(methacry1ic acid) andpoly(acry1i.c acid), whereas old data report an increase for poly(acry1ic acid) [31] and a decrease for poly(methacry1ic acid), from about 40 to 13 over the range 0.1 C an < 0.8 [19]. It is noted that due to the dependence of 1; on f (in eq.…”
Section: Association Phenomenamentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, in recent years, polyelectrolyte monomer/polymer synthesis efforts have increasingly been concentrated on quaternary polycationics 14–23. The effect of various salt ions on the interactions of polyelectrolytes in aqueous solutions has been investigated by several scholars, and the site‐binding interactions of salt ions and polymers, defined by the Huggins equation and Huggins constant k ′, has also been investigated 24–37. The counterion size has been found to affect the degree of site binding for salt‐ion‐attracting polymers.…”
Section: Introductionmentioning
confidence: 99%